La figura del cazador en las Bardenas Reales de Navarra. Estudio etnográfico de la caza en un paisaje comunal semidesértico - Mateo Pérez, M. Rosario; Orduna Portús, Pablo Miguel (Munibe Antropologia-Arkeologia, 2019)
La caza ha sido una práctica tradicional complementaria de otras actividades económicas en muchas sociedades rurales como las que han congozado en el territorio de las Bardenas Reales. Desde mitades del siglo XX se ha asistido a un repunte de su presencia en este paisaje navarro en el contexto de una moderna interpretación deportiva. Sin embargo, en esta inmensa comarca semidesértica aún se conservan algunos testimonios de aquellos cazadores que fundamentaban su labor cinegética en técnicas tradicionales. Atendiendo al examen del trabajo de campo, las fuentes orales y la documentación de archivo, este artículo recoge la información relativa a una vieja figura –la del cazador- que estuvo enmarcada en un contexto autárquico ya desaparecido en este territorio. El análisis de los datos intenta reconstruir el sistema de cacería seguido por la población local y su situación en el conjunto del patrimonio etnográfico y cultural de dicha comarca.
The figure of the hunter in the Royal Bardenas of Navarre. Ethnographic study of hunting in a semi-desert communal landscape
Hunting has been a traditional trade in many rural societies that have inhabited the Royal Bardenas. From the middle of the 20th century, there has been a rebound of hunting in the Navarrese landscape through modern amateur interpretation. However, in this immense semi-desert territory there are still some stories of hunters who hunt using traditional techniques. Using fieldwork, oral sources and historical files, this paper collects information about this ancient figure -“the hunter” - that has been framed in an autonomous context and yet has disappeared from this territory. Data analysis attempts to reconstruct possible old hunting systems followed by local hunters, placing them within the ethnographic and cultural heritage of this region. Throughout the past decades there has been a substantial change in the figure of the hunter in the Bardena. Thus, in these years, the hunting has experienced a rebound in this huge communal territory of southern Navarre. However, the presence of the job of 'traditional hunter' has disappeared in the region. It's true that before those who lived on the pieces collected constituted a minority group in the area. But, it's also true that it had its small moments of boom in periods of economic shortages - bad harvests or famines- or the need to end with certain animal pests. Thus, in the post-Spanish Civil War era, hunger gripped many humble people in that semi-desert environment. These persons chose to have their small supply of food and money with the hunt. Also, some of them didn't hesitate to use illegal techniques and hunt furtively. Even so, in the Bardena, the social value of the practice of hunting in a bunch is old and remains visible. Such the trace of them has also been indicated in the landscape through different place names. At the same time, the memory of different capture methods is maintained. Although, it's important to mention that some of the hunting techniques were abandoned or prohibited. In addition, part of a traditional knowledge linked to an old skill and a way of interacting with the balanced medium was losing. In short, then the hunter had already become a new recreational figure away from the traditional model.
Keywords: caza; cazador; Bardenas Reales; paisaje cultural; Navarra; Etnografía cinegética; hunting, hunter; Royal Bardenas; cultural landscape; Navarre; Hunting Ethnography; Scopus